2017
DOI: 10.15376/biores.12.2.2528-2547
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Partially Purified Thermostable Endoxylanase and Endoglucanase from Novel Actinomadura geliboluensis and the Biotechnological Applications in the Saccharification of Lignocellulosic Biomass

Abstract: Extracellular endoxylanase and endoglucanase from halo-and thermotolerant Actinomadura geliboluensis were produced, purified, characterized, and used in the saccharification of native and pretreated lignocellulosic biomasses. The molecular mass of endoxylanase and endoglucanase were 30 and 38 kDa, respectively. The optimum pH and temperature values for both endoxylanase and endoglucanase activities were pH 6.0 and 60 °C, respectively. They were both stable within a pH range of 4.0 to 8.0 and up to 70 °C. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Tryptone was also found to be the best organic nitrogen source for xylanase production with Bacillus subtilis sp. BS04 [ 11 ] and Geobacillus thermolevarans [ 35 ], however, yeast extract was preferred nitrogen source for xylanase production by Actinomadura geliboluensis [ 36 ], and beef extract for Bacillus pumilis SV-85S [ 7 ]. The corn steep liquor, a byproduct from wet corn milling, contains residual sugars from refining, and can be a good source of nitrogen, amino acids, vitamins, and minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Tryptone was also found to be the best organic nitrogen source for xylanase production with Bacillus subtilis sp. BS04 [ 11 ] and Geobacillus thermolevarans [ 35 ], however, yeast extract was preferred nitrogen source for xylanase production by Actinomadura geliboluensis [ 36 ], and beef extract for Bacillus pumilis SV-85S [ 7 ]. The corn steep liquor, a byproduct from wet corn milling, contains residual sugars from refining, and can be a good source of nitrogen, amino acids, vitamins, and minerals.…”
Section: Resultsmentioning
confidence: 99%
“…The media were supplemented with 50 g/L of rural agro-industrial wastes with approximately particle size of 1 mm (mesh size-20). The primary carbon source from rural agroindustrial wastes was sugarcane bagasse (50 g/L), corncob (50 g/L), rice husk (50 g/L), and sawdust (50 g/L) obtained from Davangere, Karnataka, India [26,27]. All these components were cleaned using tap water and distilled water followed by overnight drying in a hot air oven at 60°C.…”
Section: Determination Of Carbon Source For 14-β-xase Production From...mentioning
confidence: 99%
“…One unit of activity of 1,4-β-Xase is defined as, enzyme amount necessary to release 1 μmol equivalent xylose for each minute per mL at the standard conditions. Bradford assay (bovine serum albumin -standard protein) was used to examine the protein content in crude enzyme [27].…”
Section: Determination Of Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that endo-cellulase from Streptomyces argenteolus AE58P yielded 76% of glucose when biomass was pretreated with Accellerase 1500. Adiguzel and Tuncer (2017) produced endoglucanase and endoxylanase from Actinomadura geliboluensis, partially purified the enzymes and applied their mixture for saccharification of alkali-pretreated wheat straw. They achieved production of 265.12 mg/g sugars using the cocktail of hemicellulolytic and cellulolytic enzyme from the actinomycete.…”
Section: Biomass Saccharificationmentioning
confidence: 99%